Urban dynamics of commemoration and resistance. Anti-monumental memorials in Chile post-October 2019 rebellion: - Pérez González, Patricio Octavio (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The aesthetic of the memorials affiliated with the political hegemony in Chile, has developed principally emphasizing the great deeds and magnanimous names from the dominant history. For its part, the aesthetic of political resistance emerged in contexts of social protest and repression, the raising of the figures of the dead, forgotten names, women and characters excluded from the account of traditional memory. From the study of the city, understood as a bordered space, where the accounts of the memories of hegemonies and resistance strain, this work proposes a theoretical and empirical discussion of the anti-monumental aesthetic, applied to the memorial erected in Santiago de Chile in homage to Mauricio Fredes, which is manifested as the text that subverts the feelings of commemoration, from the resistance. In this way, this work offers a reading from the perspective of the history of the present time, of the political, economic and social conditionsthat form the base of the wave of protests that occurred in Chile in October of 2019, which resulted in the death of Fredes, among others, whom the aesthetic of the memories of the resistance commemorate.